Iron-Catalyzed Alkylation of Alkenes and Alkynes Using Alcohols as the Alkylating Reagent - Shang, Xiaojie; Liu, Zhong-Quan (Synthesis, 2015)
Recent developments in iron-catalyzed C–C bond formation through the coupling of alkenes and alkynes with alcohols are highlighted here. Alcohols are used as effective alkylating reagents in these systems, which is potentially very attractive in modern synthetic organic chemistry.
Keywords: alcohols; alkylation; alkenes; alkynes; iron